Varför föddes det få barn på 1990-talet? : fruktsamhet, familjepolitik och sysselsättning - Olsson,Anna (2002)
The purpose of this essay was to study explanations to why few children were born in Sweden in the 1990´s. The purpose was also to look at different political actions to stimulate childbearing. My essay is a literature study and in my work I have used available statistics and already existing research. The total fertility rate in Sweden is because of how the family policy is constructed strongly connected to the situation on the labour market. During the 1990´s when the unemployment rates were high many young adults postponed their childbearing and the total fertility rate decreased. Most young adults want to have children in the future so when the situation on the labour market improves the total fertility rates is expected to increase. During the 1990´s the first time mothers were older than ever before and that will affect the complete fertility rates. Sweden has during the 20 th century been the only country in Europe which has not had a decreasing complete fertility rate. In Sweden the complete fertility rate has been stable around 2.0 children per women, a stability which is explained by the Swedish family policy that makes it possible to combine family and labour work.
Keywords: Social problems and welfare, national insurance; Sociala problem, social välfärd, socialförsäkring